Acid-reducing vagotomy is associated with reduced risk of subsequent ischemic heart disease in complicated peptic ulcer: An Asian population study. Issue 50 (December 2016) - Wu, Shih-Chi; Fang, Chu-Wen; Chen, William Tzu-Liang; Muo, Chih-Hsin
Abstract : Abstract: Persistent exacerbation of a peptic ulcer may lead to a complicated peptic ulcer (perforation or/and bleeding). The management of complicated peptic ulcers has shifted from acid-reducing vagotomy, drainage, and gastrectomy to simple local suture or non-operative (endoscopic/angiographic) hemostasis. We were interested in the long-term effects of this trend change. In this study, complicated peptic ulcer patients who received acid-reducing vagotomy were compared with those who received simple suture/hemostasis to determine the risk of ischemic heart disease (IHD). This retrospective cohort study analyzed 335, 680 peptic ulcer patients recorded from 2000 to 2006 versus 335, 680 age-, sex-, comorbidity-, and index-year matched comparisons. Patients with Helicobacter pylori (HP) infection were excluded. In order to identify the effect of vagus nerve severance, patients who received gastrectomy or antrectomy were also excluded. The incidence of IHD in both cohorts, and in the complicated peptic ulcer patients who received acid-reducing vagotomy versus those who received simple suture or hemostasis was evaluated. The overall incidence of IHD was higher in patients with peptic ulcer than those without peptic ulcer (17.00 vs 12.06 per 1000 person-years), with an adjusted hazard ratio (aHR) of 1.46 based on multivariable Cox proportional hazards regression analysis controlling for age, sex, Charlson's comorbidity index, and death (competing risk). While comparing peptic ulcer patients with acid-reducing vagotomy to those with simple suture/hemostasis or those without surgical treatment, the aHR (0.58) was the lowest in the acid-reducing vagotomy group. Patients with peptic ulcer have an elevated risk of IHD. However, complicated peptic ulcer patients who received acid-reducing vagotomy were associated with reduced risk of developing IHD.